Interstrand crosslinking oligonucleotides elucidate the effect of metal ions on the methylation status of repetitive DNA elements - Liu, Shan; Morihiro, Kunihiko; Takeuchi, Fumika; Li, Yufeng; Okamoto, Akimitsu (Frontiers in Chemistry, 2023)
DNA methylation plays an important physiological function in cells, and environmental changes result in fluctuations in DNA methylation levels. Metal ions have become both environmental and health concerns, as they have the potential to disrupt the genomic DNA methylation status, even on specific sequences. In the current research, the methylation status of two typical repetitive DNA elements, i.e., long-interspersed nuclear element-1 (LINE-1) and alpha satellite (α-sat), was imaged and assessed using methylation-specific fluorescence in situ hybridization (MeFISH). This technique elucidated the effect of several metal ions on the methylation levels of repetitive DNA sequences. The upregulation and downregulation of the methylation levels of repetitive DNA elements by various metal ions were confirmed and depended on their concentration. This is the first example to investigate the effects of metal ions on DNA methylation in a sequence-specific manner.